Effectiveness of a community football programme on improving physiological markers of health in a hard-to-reach male population: the role of exercise intensity. (3rd March 2016) - Hulton, Andrew Thomas; Flower, David; Murphy, Rebecca; Richardson, Dave; Drust, Barry; Curran, Kathryn
Abstract : The present study evaluated the effectiveness of participation in recreational football during a community health programme, on physiological markers of health within a hard to reach population. Nine men (Age: 33 ± 9 years, Mass: 75.4 ± 13.7 kg, Height: 1.74 ± 0.07 m and Body Fat: 19 ± 2%) were recruited to participate in the study in collaboration with an English Premier League Football Club. Participants completed the 12-week football-based programme which included two coached football sessions each week. Physiological tests for blood pressure, resting heart rate, cholesterol and an anthropometrical test for body composition were completed at three time points during the study (Weeks – 1, 6 and 12) in an attempt to evaluate the impact of the intervention on health. During each training session, measurements of intensity (%HRmax, identified from the yoyo intermittent level 1 test), duration and rating of perceived exertion were made. The 12-week programme (mean HRmax throughout programme = 75 ± 4% beats min −1 ; mean RPE throughout programme = 6 ± 1) elicited few changes in physiological markers of health with the only significant change been a decrease in resting heart rate from weeks 6 to 12 (87 ± 22 beats min −1 at week-6, to 72 ± 17 beats min −1 ; p < 0.05). These data would suggest that the current community football-related health project was not effective in improving physiological markers of health, but was able to maintain their level of health. A lack of improvement may be due to the low intensity of sessions and a lack of coach education for the promotion of sessions that aim to improve health.